Memory-enhancing, anxiolytic and antidepressant effects of inhaled Achillea biebersteinii essential oil on scopolamine-induced amnesic rats - Akbaba, Emel; Bağcı, Eyüp; Salam, A. Hassan (My University, 2017)
In this study, we investigated the possible neuroprotective effects of Achillea biebersteinii (Asteraceae) volatile oil. The plant is a shrub, distributed in South-west Asia, South-eastern Europe, and Northern Africa. It is an aromatic and medicinal plant and has been used traditionally to treat several conditions in Turkey and in the World. The present research investigates the memory enhancing, anxiolytic and antidepressant effects of Achillea biebersteinii essential oil on scopolamineinduced amnesic rats. Y-maze and radial arm maze tasks were used for evaluating memory formation. Likewise, anxiety and depressive-like behavior were conducted by elevated plus-maze and forced swimming tasks, respectively. Scopolamine-treated rats reduced memory formation as evidenced by decreased spontaneous alternation percentage in Y-maze test, and increased working memory errors and reference memory errors in radial-arm maze test. Achillea biebersteinii volatile oil significantly increased spontaneous alternation percentage, and decreased the working memory errors and reference memory errors. Furthermore, scopolamine-alone treated rats exhibited anxiety and depressive-like behavior as evidenced by reduced percentage of open arm time, number of open arm entries and number of crossings in the elevated plus maze and the swimming time and immobility time in the forced-swimming test. Achillea biebersteinii volatile oil increased the percentage of open arm time, number of open arm entries and number of crossings in the elevated plus maze, and increased the swimming time and decreased the immobility time in the forced-swimming test in scopolamine administered rats as compared to scopolamine-alone treated rats. Hence, this study suggests that the multiple exposures of Achillea biebersteinii volatile oil ameliorate scopolamine-induced spatial memory formation, anxiety and depressive-like behavior. In conclusion, Achillea biebersteinii essential oil may be useful alternative or complementary choice in either the protection or the treatment of neurodegenerative diseases such as Alzheimer's disease.
Bildiri - Yayımlanmış
Keywords: Achillea biebersteinii essential oil; Alzheimer’s disease; Scopolamine; Memory; Anxiety; Depression